A comparison between the Companies Acts of 1926 1973 and 2008 in respect of pre-incorporation contracts in relation to the stipulation alteri - Joubert, E.P. (University of Pretoria, 2018)
Mini Dissertation (LLM)--University of Pretoria, 2018.